Design and synthesis of hollow nanostructures as highly efficient hosts for advanced lithium-sulfur/selenium sulfide batteries - Zhang, Jintao (2019)
Due to the overwhelming superiorities in energy density and material cost, lithium-sulfur (Li-S) batteries have been recognized as a potential candidate for next-generation electrochemical energy-storage (EES) technology. The main challenges for Li-S batteries lay in the enhancement of reaction kinetics and the suppression of the polysulfide dissolution at high S loading electrodes. In the first two projects, we have focused on the host materials. Two types of novel hollow nanostructures have been successfully designed and synthesized as efficient hosts for S to improve the electrochemical performance of Li-S batteries. After that, we have used SeS2 instead of S as the active material to further enhance the performance of Li storage. It is proved that the introduction of a certain proportion of Se into S-based cathodes could obviously improve the integrated battery performance. The main results and new findings in this work are summarized as follows. 1. Double-shelled nanocages with inner Co(OH)2 shell and outer LDH shell (CH@LDH) have been designed and synthesized as a conceptually new sulfur host for Li-S batteries. Specifically, the hollow CH@LDH polyhedra with complex shell structures not only maximize the advantages of hollow nanostructures for encapsulating a high content of sulfur (75wt%) but also provide sufficient self-functionalized surfaces for chemically bonding with LiPSs to suppress their outward dissolution. When evaluated as cathode material for Li-S batteries, the CH@LDH/S composite shows a significantly improved electrochemical performance. 2. Hollow Ni/Fe LDH polyhedrons have been designed and fabricated as an advanced sulfur host for enhancing the performance of Li-S batteries. The Ni/Fe LDH host shows multiple advantages. First, the Ni/Fe LDH shells can provide sufficient sulfiphilic sites for chemically bonding with LiPSs. Second, the hollow architecture can provide sufficient inner space for both loading a large amount of sulfur and accommodating its large volumetric expansion. Moreover, once the active material is confined within the host, the shells could easily restrict the outward diffusion of LiPSs, guaranteeing prolonged cycle life even with high sulfur loading. As a result, the S@Ni/Fe LDH cathode has successfully solved the main issues related to sulfur electrodes, and it exhibits significantly improved electrochemical performances with prolonged life over 1000 cycles and excellent rate properties. 3. A freestanding lotus root-like carbon fiber network decorated with CoS2 nanoparticles (denoted as CoS2@LRC) has been designed and prepared as the SeS2 host for enhancing the lithium storage performance. The integrated electrode is constructed by 3D interconnected multichannel carbon fibers, which can not only accommodate high content of SeS2 (70 wt %), but also promise excellent electron and ion transport for achieving high capacity utilization of 1015 mAh g-1 at 0.2 A g-1. What is more, there are numerous CoS2 nanoparticles decorated all over the inner walls and surfaces of the carbon fibers, providing efficient sulfiphilic sites for restricting the dissolution of LiPSs and LiPSes during the electrochemical processes, thus successfully suppressing the shuttle effect and maintaining excellent cycling stability over 400 cycles at 0.5 A g-1.